Structuring the European administrative space: channels of EU penetration and mechanisms of national change - Heidbreder, Eva G. (2009)
Abstract: "The author provides an analytical model to capture mechanisms of supranational impact on national public administrations. The aim is to understand how we can perceive a European administrative space given the persistent diversity between member states. In face of the overly complex subject matter, it is argued that a typology that presents ideal types of interaction modes between supranational and national levels of administration provides in fact a suitable pragmatic approach to understand the potential impact of European integration on national civil services. Scrutinizing which mechanisms of possible influence-taking the European Union (EU) invokes shows that administrative integration does actually not suggest overall convergence. Instead the shared administrative space works precisely because it preserves state-sensitive diversity. Only in the context of enlargement did the EU need to present a single model to the candidate states and thus the notion of an ever more convergin